The effect of problem based learning model in science process skills on respiratory system materials - Martin, Dliya Syahirah Eka; Susanti, Rahmi; Destiansari, Elvira; Madang, Kodri (Universitas Negeri Jakarta, 2025)
This research aims to determine the effect of problem-based learning (PBL) learning model on the science process skills (SPS) of grade XI students on respiratory system material. This research used quantitative method with pre-experimental design. Biology learning requires student-centered learning to improve students' science process skills. However, students are rarely involved in teaching and learning activities. The low level of participation of students in biology learning causes the science process skills of students to be less emphasized. The research was conducted by applying the PBL model to class XI.7 at SMAN 1 Palembang with respiratory system learning material. The instruments used included pre-test and post-test SPS tests, as well as a questionnaire sheet for students' responses to learning using PBL. Data analysis was done by normality test, paired t-test, effect size test, and N-gain test. The results showed that there was a significant effect on students' SPS with learning using the PBL model. The PBL model has a positive influence in improving the SPS aspects of observing, classifying, concluding, predicting, and communicating. This is supported by the results of filling out a questionnaire of students' responses to learning using the PBL model as a whole giving a very good response to PBL. This research can be further developed by using further research designs, such as research using a control class to determine the comparison of the effectiveness of PBL models with other learning models